Comprehension in interpreting and translation: testing the phonological interference hypothesis. (4th July 2019) - Díaz-Galaz, Stephanie; Torres, Alejandro
ABSTRACT: Studies on the comprehension process in interpreting have shown that concurrent processing reduces recall in simultaneous interpreting. This effect has been attributed to phonological interference: since the articulatory loop is busy with the parallel vocalization of two streams of speech, encoding is impaired to such an extent that interpreters are not able to remember much of what they have just interpreted. On the other hand, recent studies on the translation process show that comprehension and production overlap in written translation in a way that is similar to simultaneous interpreting. Therefore, this article examines the role of phonological interference in written and oral translation to determine whether or not it also hinders recall in written translation, and to gauge how task requirements affect the comprehension process in translation and interpreting. In this study, comprehension was measured through summarization, multiple choice comprehension questions and cloze questions administered after simultaneous interpretation and translation activities were completed by a group of advanced interpreting students. Results suggest that both translation and interpreting share similar features regarding parallel processing and, furthermore, that the process of comprehension is influenced by the demands associated with translation and simultaneous interpreting.